Study on developments of body composition and physical fitness for a year in japanese adolescent track and field athletes - Miyamoto, A.; Umezawa, J.; Yanagiya, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
It is well known that physical fitness develops with the increased muscle thickness in adolescent boys especially from 16 to 18 years. Fukunaga et al. (1989) investigated the developments of body composition in Japanese boys and girls, and revealed that the muscle and fat cross sectional area increased with age from 16 to 18 years. Seefeldt et al. (1986) had reported that vertical jump height and maximal running velocity improved linearly with age from 5 to 18 years in boys who had no habitual physical training. However, no studies have investigated development of physical fitness of adolescent athletes. In addition, duration of measurement of longitudinal studies was a year basically. It is necessary to assess physical fitness several times within a year.The purpose of this study was to investigate developments of body composition and physical fitness in Japanese adolescent track and field athletes.